PERSEPSI SISWA TERHADAP MANFAAT PELAKSANAAN PRAKTEK KERJA INDUSTRI DI SMK N 1 LEMBAH GUMANTI - Fitria Syahroni (Universitas Negeri Padang, 2014)
This study aimed at describing about student’s perception of industrial practice used of student’s confidence, profesionality, relevantion of material with knowladge and prepare the student to come in to the work. Phenomena in the background shows many students are not obey of school regulation, many of them can’t solve the assigment about their surface and there are many unemployed after they graduated frrom SMK. The population is 59 students of SMK N 1 Lembah Gumanti (grade XII). Samples taken were 100% of the total population of 59 people. The instrument used in this study is a questionnaire that has been sampled validity and reliability. In general, the student's perception of the practice industrial's used of SMK N 1 Lembah Gumanti in the category quite well with the over all average percentation was 74.86%. Kata kunci: industrial practice